2012
DOI: 10.1111/j.1469-8749.2012.04251.x
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory activity of children with cerebral palsy: which characteristics are important?

Abstract: Aim  To assess ambulatory activity of children with cerebral palsy (CP), aged 7 to 13 years, and identify associated characteristics. Method  Sixty‐two children with spastic CP (39 males, 23 females; mean age 10y 1mo, SD 1y 8mo; age range 7–13y), classified as Gross Motor Function Classification System (GMFCS) levels I to III, participated. Ambulatory activity was measured during 1 week with a StepWatch activity monitor as steps per day, and time spent at medium and high step rates. Multiple linear regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 28 publications
5
59
0
Order By: Relevance
“…Daily physical activity levels of people with cerebral palsy (CP) are low [1,2]. Like the rest of the population, low levels of physical activity increases the risk of people with CP developing secondary health problems such as cardiovascular diseases, obesity or osteoporosis [3].…”
Section: Introductionmentioning
confidence: 99%
“…Daily physical activity levels of people with cerebral palsy (CP) are low [1,2]. Like the rest of the population, low levels of physical activity increases the risk of people with CP developing secondary health problems such as cardiovascular diseases, obesity or osteoporosis [3].…”
Section: Introductionmentioning
confidence: 99%
“…Management of gait dysfunction in patients with cerebral palsy may include nonoperative measures, such as physiotherapy [45], orthotics [5], casting [19], and injections of botulinum toxin type A [17]. Despite appropriate nonoperative management, however, the majority of patients with spastic diplegia will have fixed contractures and bony deformities develop which require surgical correction to maintain gait or even sitting functions.…”
mentioning
confidence: 99%
“…The descriptive literature supports a social model, studying the person in the context of environment, versus a medical model, which focuses on the context of disability (Colver et al, 2012;Palisano et al, 2009;van Wely, Balemans, Becher, & Dallmeijer, 2014). Study findings reported that environmental variables (accessibility, attitude, adaptations) were found to be as effective for improving self-help skills and mobility as conventional therapeutic interventions focused on changing the child (Colver et al, 2012).…”
Section: Methods To Engage Adolescents With Cerebral Palsy In Physicamentioning
confidence: 97%
“…Virtual reality systems also hold interest and motivate longer sessions of physical activity (Bryanton et al, 2006). Barriers to physical activity include a variety of factors such as physical (inaccessibility), programmatic (lack of knowledgeable staff), attitudinal (over-emphasis on competition and winning), as well as a lack of understanding for personal and environmental factors (Colver et al, 2012;Donkervoort et al, 2006;van Wely, Becher, Balemans, & Dallmeijer, 2012). Several investigators recommend these areas as targets for change.…”
Section: Methods To Engage Adolescents With Cerebral Palsy In Physicamentioning
confidence: 99%
See 1 more Smart Citation